Libraries of the University of the Philippines problems and ergonomic solutions - Hao, Holden Manos; Cruz, Agerico V. (1992.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: University of the Philippines (Diliman) Libraries; Academic libraries -- Philippines -- Quezon City -- Designs and plans